A Lightweight Trust Scheme for Iot - S. Chithra, Dr; N. Bhalaji, Dr; Nandini, S (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) refers to system in which smart objects interact with each other with the aid of sensors and actuators through wired/wireless connection. When an IoT concept is implemented for real life application, the possibility of the system being attacked increases. The security measures have to be improved to prevent the attacks.  This paper introduces light weight security schemes for authentication and encryption.  This system uses Blom’s scheme for authentication and Elliptic curve cryptography for encryption. Both these schemes are claimed to be light weight and hence is applicable of IoT applications which is a constrained environment.  These security schemes are applied for healthcare system. The system is proved to be strong against the security attacks.